Womenomics: Gender Inclusivity as a Growth Strategy in Japan - Janice Elysia; Ni Putu Juniari; Ni Luh Putu Cintya Devi (Jurnal Transformasi Global, 2023)
As a developed country, Japan is not immune to difficulties. Hyper-aged population, economic stagnation, and gender inequality are some of the crucial issues. The presence of the Womenomics policy in 2013 as an effort to empower women in Japan is one of the Japanese government's solutions to mitigate the problem of hyper-aged population, economic stagnation, and gender disparity. This research aims to discover and examine the challenges of the 21st century in Japan, particularly the subject of women's empowerment and its correlation with economic growth. The descriptive qualitative case study research method was applied to examine the political goods within the Womenomics policy. With a public policy approach, the study's findings represent Japan's efforts to implement an gender-based innovative policy that allows Japanese women to access equal opportunities in social, political, education, and economic sectors to increase the labour force number as the growth strategy to mitigate the impact of the hyper-aged population in Japan. This policy shows that Japanese women have grown in the workplace, however many challenges still occur to tackle the gender-biased paradigm in Japanese society, such as wage-gap problems. KEYWORDS: Japan; Gender Inclusivity; Innovative Policy; Womenomics